Effect Of Lanthanum Dopant On The Properties Of Cacu3ti4o12 Thin Films Synthesized By Sol-Gel Method - Ahmad, Nurul Nasuha (2012)

(untitled)
The CaCu3Ti4O12 (CCTO) was discovered to possess high dielectric constants, ɛ ~ 104 at low frequencies. The undoped and La doped CCTO thin films were prepared by sol-gel method. The raw materials of Ca(CH3COO)2, Cu(C2H3O2)2.H2O, Ti[OCH(CH3)2]4, were used to produce undoped CCTO thin films, whereas La(NO3)3.6H2O was used as dopant source to form La-doped CCTO (Ca1-xLaxCu3Ti4O12) with x = 0.01, 0.02, 0.05 and 0.10. The sol-gel solution was heated for two and half hours at 110 °C and then deposited on the p type Si wafer using spin coating process. The dried films were annealed using two stages of annealing process at 500 °C for 10 minutes and followed by at 900 °C for 1 hour. The phase formation of the CCTO was identified by X-ray diffraction (XRD) and the microstructure observed by field emission scanning electron microscope (FESEM). The elemental composition of prepared CCTO thin films was identified by using energy dispersive X-ray (EDX). The topography and the phase imaging of the samples were obtained using atomic force microscopy (AFM) by scanning area of 10 μm x 10 μm. The semiconductor parameter analyzer (SPA) was used to measure the current-voltage (I-V) and capacitance-voltage (C-V) characteristics. The samples were coated with silver electrodes for electrical and dielectric properties measurement. The formation of CCTO compound was confirmed by XRD with some minor peaks of CuO and TiO2 co-exist in CCTO thin films. The grains size is in between 38 nm to 205 nm measured by SEM. The EDX analysis confirmed the chemical element of CCTO exist in the thin films. The AFM analysis confirmed no significant secondary phase observed from the phase imaging of the film surface. Sample doped with 2 at% La give better electrical conductivity. The La dopant shows improvement on the dielectric properties of the CCTO with 2 at% La give optimum dielectric value.